Analysis and countermeasure to improve a low takt production item based on LPS evaluation at Hicom Teck See Sdn. Bhd. - Muhammad Quyyum, Sohaimi (2012)
Toyota Production System (TPS) is derived from Toyota's original idea was just in time (JIT) which it is the idea of sakiichi Toyoda, Toyoda kinchiri their engineers, taiichi Ohno. Objective of this system is to design out a muda (waste), mura (inconsistency) and muri (work load). In Malaysia this system at first adopted in the automotive industry, especially in Proton and Perodua as well as their vendors. Hicom Teck See (M) Sdn. Bhd. is one of the Proton and Perodua vendors that produce parts made from plastic as the front bumper. From the results of evaluation of LPS in May 2011, Takt Production showed the lowest criteria, in order to solve this problem one of the seven QC tools are used, next by used CFMEA and FMEA for determined the potential of the root causes why the production is the lowest criteria. By obtaining these potentials occur this problem, suggestions for improving these criteria are shown. By taking one of the products produced Hicom Teck See, a case study have been done. For this case study, a visits to Hicom Teck See have been done, all data on these products is taken to produce a proposal. The proposal is expected to improve Takt production criteria, and thus increase the score assessment of LPS in the next evaluation. By prepare proposals, Hicom Teck can see self-improvement / kaizen at work stations to reduce the lead time to customers and reduce the workload on the operator.